ПРОДУКТИВНІСТЬ СИНТЕЗУ ЕКЗОПОЛІСАХАРИДУ BACILLUS MUCILAGINOSUS ЗАЛЕЖНО ВІД ДЖЕРЕЛА АЗОТУ І ПОХОДЖЕННЯ ПОСІВНОГО МАТЕРІАЛУ - Малиновська, І. М. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2015)
It was established that Bacillus mucilaginosus C-3 requires introduction of nitrogen sourceinto the culture medium in form of nitrate as themost optimal for maximal accumulation of bacterial biomass and sporulation process. Introduction of the ammonium form was less efficient. It was shown that the intensity of nitrogensource use by B. mucilaginosus is highly depended on the physiological state of the inoculum cells. At sowing of spore inoculum theoptimal concentration of potassium nitrate was2.5 g/l resulting in 1010 cells/ml, while under theuse of vegetative cells the optimal concentrationof potassium nitrate was 1.0 g/l leading to theaccumulation of 109 cells/ml.Use of spore inoculum had ensured themaximum productivity of extracellular polysaccharide synthesis. With the higher number ofB. mucilaginosus subcultures in a vegetativestate the efficiency of the exopolysaccharidesynthesis has decreased: after the second passage — by 20.0 %, after the fourth — by 56.5 %,after the sixth — at 127.8 %. After eighth passage the culture loses its ability to synthesizepolysaccharide, especially on the medium withthe N : C ratio 1 : 3 and resume this ability onlyafter sporulation and the significant increase ofthe N : C ratio.